Rekultywacja oraz zagospodarowanie leśne wyrobisk po eksploatacji kruszyw naturalnych w regionie środkowopomorskim = Recultivation and afforestation of natural aggregate excavation grounds in środkowe pomorze - Harabin, Zdzisław; Pulkowski, Witold; Wrona, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the most numerous group of postindustrial waste land create to the excavations accompanying to mine of natural resources, mostly of sand and of gravel applied in construction and road building in Poland. It estimates oneself, that in present moment on the area of country the number of this kind of post-exploitation emptiness steps out beyond 30thousands. Most of them are not developed So in some regions of country these waste lands determine serious economic and ecological problem.
Keywords: rekultywacja gruntów pokopalnianych; Pomorze Środkowe